Nanostructured gold coating for prevention of biofilm development in medical devices - Rocca, Diamela María (2019)
Bacterial biofilms on medical devices (MDs) can cause deadly infections due to their resistance to antibiotics. Technology to prevent this kind of complication is urgently needed because they impact not only patients' lives but also hospital budgets. In this article, the creation and testing of an easy-to-produce antibiofilm (more precisely antibiofouling) coating are described for the first time. This coating can be applied to catheters, prostheses, and other plastic pieces, even after they have been manufactured. Rapid and ecofriendly synthesis of nanostructured gold coating was done in situ in just 15 minutes. Complete characterization and microbiological analysis of its antibiofouling capacity are presented. The coating prevents biofilm formation of pathogenic clinical isolates and ATCC strains on MDs, possibly due to its complex nanostructured gold surface. If the next generation of MDs is coated with this kind of antibiofouling technology, biofilm-related infections could be dramatically reduced.